The Need to Recalibrate the Scales: Balancing Secularism and the Right to Wear a Hijab in Europe - Horsley, Lia (Victoria University of Wellington Law Review, 2025)
The European Convention on Human Rights protects the fundamental right to manifest one's religious beliefs, including protecting a Muslim woman's right to wear a hijab. Nevertheless, some member states have prohibited Muslim women from wearing a hijab in certain contexts to safeguard the principle of secularism, and the European Court of Human Rights (ECtHR) has upheld these restrictions in four key cases. This article argues that the Court's decisions in these cases are not justifiable as the Court has conducted an inadequate analysis of the necessity and proportionality of the restrictive measures and applied an unduly wide margin of appreciation. It also argues that some member states may be relying upon abstract aims like "secularism" and "living together" as a façade to disguise hostility toward Islam and that the Court has been unwilling to address this concern. This article concludes with three recommendations for reform that aim to address the flaws in the Court's analysis and allow the Court to strike a more appropriate balance between state autonomy and the protection of fundamental individual rights. These reforms are necessary to promote tolerance in Europe and prevent states from relying on abstract principles to unduly restrict individual rights.